Psychoemotional states under pandemics / Stări psihoemoționale asociate situației pandemice - BALODE Neli (EcoSoEn: Ştiinţe Economice, Sociale şi Inginereşti = Economics, Social and Engineering Sciences)
Loneliness is a subjective feeling anyone experienced in certain periods of their life. Nowadays, because of pandemic restrictions the usual face-to-face communication people use, has been massively substituted by the virtual communication. Not surprisingly such circumstances affected the population psychological well-being globally, exacerbating the feeling of loneliness, anxiety and depression. The survey, which was conducted between March - December 2020, was aimed at investigating the feeling of loneliness and associated emotional states under pandemic restrictions. The research sample consisted of 45 subjects, adults aged from 23 to 34, who were asked to complete a number of questionnaires, i. e. UCLA Scale to measure loneliness, Spielberger Anxiety Questionnaire and Beck Depression Inventory. Participants completed the questionnaires twice, first in March 2020 when pandemic restrictions were launched, then in December 2020 when restrictions were relaxed and people got used to preventive measures against pandemics. We also asked participants to indicate what kind of news about the virus they were mainly focused on: a) news emphasizing exclusively the threats and danger of the new virus; b) news relating about the research, findings and scientific progress made in understanding the new virus; 3) avoid reading any news related to pandemics and the virus. Our research data show that the level of loneliness, anxiety (both Trait and State) and depression were significantly higher in March as compared to the same in December 2020. Data also revealed that subjects who scored higher in March on Anxiety as a Trait reported the same high level of Loneliness and Depression in December. The kind of news about the virus subjects were focused on wasn't a significant factor for the emotional states associated with loneliness. Thus, people who have an elevated anxiety-trait are at a higher risk for developing emotional disorders and in a greater need of a psychological support.